The tourism potential of board regions - endogenous resources and destination image evaluation - J. A. Cadima Ribeiro; Laurentina Cruz Vareiro; Carmen Padin Fabeiro; Xulio Pardellas de Blas (European Regional Science Association (ERSA), 2005)
Tourism has an enormous potential while instrument of regional development. However, the opportunities are not the same for each territory and it is easy to understand that, considering the resources available, not every region has the choice to base its development strategy in the touristic industry. Taking this in consideration, the mission of classifying, evaluating and compare, from a consistent and realistic point a view, several groups of tourist resources became a necessary task and a precondition to define the touristic vocation of a region. This approach allows to select the best alternative to tourism development. The paper attempts to catalogue the tourist resources of the selected territory and to evaluate the different sort of resources available, using several classification approaches, aiming to calculate its index of touristic potential. We believe that the before mention methodology might be a valuable instrument to identify the strongnesses and weaknesses of the Minho-Lima sub-region (Portugal) in what refers to its touristic development, as well as the degree of integration of the tourism sector in the local productive system.
Keywords: 330